Handling and performance characteristics of a new small caliber radiopaque embolic microsphere - Lewis, Andrew L. (J Biomed Mater Res B Appl Biomater, 2020)
The in vitro and in vivo handling and performance characteristics of a small caliber radiopaque embolic microsphere, 40–90 μm DC Bead LUMI™ (LUMI40‐90), were studied. Microsphere drug loading and elution and effects on size, suspension, and microcatheter delivery were evaluated using established in vitro methodologies. In vivo evaluations of vascular penetration (rabbit renal artery embolization), long‐term biocompatibility and X‐ray imaging properties, pharmacokinetics and local tissue effects of both doxorubicin (Dox) and irinotecan (Iri) loaded microspheres (swine hepatic artery embolization) were conducted. Compared to 70–150 μm DC Bead LUMI (LUMI70‐150), LUMI40‐90 averaged 70 μm versus 100 μm, which was unchanged upon drug loading. Handling, suspension, and microsphere delivery studies were successfully performed. Dox loading was faster (20 min) and Iri equivalent (<10 min) while drug elution rates were similar. Contrast suspension times were longer with no delivery complications. Vascular penetration was statistically greater (rabbit) with no unexpected adverse safety findings (swine). Microspheres ± drug were visible under X‐ray imaging (CT) at 90 days. Peak plasma drug levels and area under the curve were greater for LUMI40‐90 compared to LUMI70‐150 but comparable to 70–150 μm DC BeadM1™ (DC70‐150). Local tissue effects showed extensive hepatic necrosis for Dox, whereas Iri displayed lower toxicity with more pronounced lobar fibrosis. LUMI40‐90 remains suspended for longer and have greater vessel penetration compared to the other DC Bead LUMI sizes and are similarly highly biocompatible with long‐term visibility under X‐ray imaging. Drug loading is equivalent or faster with pharmacokinetics similar to DC70‐150 for both Dox and Iri.